ASSESSING THE ROLE OF FINANCIAL RISK MANAGEMENT IN CORPORATE DECISION-MAKING - Alfiana, Alfiana; Hendrawan, Henky; Siddiqa, Heidi (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This paper aims to assess the role of financial risk management (FRM) in corporate decision-making, emphasizing its importance in ensuring sustainable business practices. Financial risk management involves identifying, analyzing, and mitigating risks that may affect an organization's financial health. This literature review examines various studies and theories that explore how FRM contributes to corporate decision-making processes, particularly in areas such as investment decisions, capital budgeting, and strategic planning. The review highlights the relationship between risk management practices and organizational success, demonstrating how effective risk management can enhance decision-making by providing a structured approach to uncertainty. The findings suggest that integrating FRM into corporate strategies can lead to improved financial stability, better resource allocation, and increased shareholder value. This paper concludes by proposing areas for future research on the integration of risk management practices into corporate governance and decision-making frameworks.